Numerical Simulations of Solid Circulation Characteristics in an Internally Circulating Elevated Fluidized Bed. Issue 4 (17th March 2017) - Hassan, Muhammad; Schwarz, M. Philip; Rafique, Muhammad; Feng, Yuqing; Liu, Guodong; Witt, Peter J.; Wang, Shuai; Lu, Huilin
Abstract: A twin‐chamber internally circulating elevated fluidized bed (EFB) with one chamber elevated higher than the other within a single vessel is simulated using a two‐fluid model. Two EFB configurations termed as reaction chamber (RC)‐elevated and heat exchange chamber (HEC)‐elevated is evaluated. The effect of chamber elevation, variation of superficial velocities, and interchanging the two chambers are investigated and the results are quantified in terms of solid flux G s . By increasing the RC gas velocity U R at constant HEC velocity U H, Gs is increased in both EFBs while an opposite behavior is observed by increasing U H at constant U R . Variation of the chamber elevation as well as interchanging the chambers also affects the performance of the two EFBs. Abstract : Solid circulation behavior in a twin‐chamber internally circulating elevated fluidized bed is predicted using a two‐fluid model. One chamber is elevated higher than the other within a single vessel. The solid circulation rate is higher than in a conventional non‐elevated internally circulating fluidized bed and depends on the chamber superficial velocities and elevation.